Second chance summer - Matson, Morgan (Simon & Schuster Books For Young Readers, 2012)
"Taylor Edwards' family might not be the closest-knit--everyone is a little too busy and overscheduled--but for the most part, they get along just fine. Then Taylor's dad gets devastating news, and her parents decide that the family will spend one last summer all together at their old lake house in the Pocono Mountains. Crammed into a place much smaller and more rustic than they are used to, they begin to get to know each other again. And Taylor discovers that the people she thought she had left behind haven't actually gone anywhere. Her former best friend is still around, as is her first boyfriend...and he's much cuter at seventeen than he was at twelve. As the summer progresses and the Edwards become more of a family, they're more aware than ever that they're battling a ticking clock. Sometimes, though, there is just enough time to get a second chance--with family, with friends, and with love"--